The Influence of Customer Knowledge and Perceived Value on the Decision to Become a Participant and not a Wage Recipient in BPJS Ketenagakerjaan Pekanbaru Panam Branch - Desnor Linda; Mandataris (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to determine the influence of Customer Knowledge and Perceived value on the decision to become a Non-Wage Recipient Participant at BPJS Employment Pekanbaru Panam Branch. The method used in this research is descriptive and quantitative statistics with an explanatory research model. The sample in this study consisted of 100 respondents determined by convenience sampling and using a questionnaire as a data collection instrument. The analysis tool in this research uses PLS-SEM. From data analysis which includes Validity Test, Reliability Test, PLS-SEM Model Evaluation, Structural Model Evaluation, Hypothesis Testing, the results obtained are that Customer Knowledge has a positive and significant influence on the Decision to Become a Participant and Perceived value has a positive and significant influence on the decision to become a participant.